THE ROLE OF COOPERATIVES IN RETIREMENT EMPLOYEES AT THE LHOKSEUMAWE NASARI SAVING AND LOAN COOPERATIVE. COOPERATIVE OBJECTIVES: PROSPERITY OF MEMBERS - Sri Hayu Kartika; Riska Fazira; Yusril Ramadhan Sembiring; Irada Sinta; Rico Nur Ilham (RADJA PUBLIKA, 2022)
Indonesia has many Civil Servants (PNS), the Indonesian National Armed Forces and the Indonesian National Police (Polri) who are sure to retire every year. Based on data from the National Civil Service Agency (BKN), Thursday (12/11/2020), in the 2021-2024 period there are around 706,438 civil servants who will retire. In 2021, there are 162,484 employees who will retire either because of the retirement age limit (BUO) or non-bup, which makes many financial institutions focus on serving these retirees. One of them is the Nasari Savings and Loans Cooperative which focuses on providing services to retirees in Indonesia. As well as remembering and Departing from the economic crisis that hit Indonesian society in 1998, a group of retirees who cared about the situation at that time, established a Savings and Loans Cooperative (KSP) named NASARI. The aim is to provide solutions to retired civil servants, military, police in addressing their needs in their old age.The Nasari Lhokseumawe Cooperative seeks to improve the welfare of its members, namely retired employees by using several strategies, namely Improving the Welfare of its Members by improving Services to Members and facilitating the Administrative process, Improving the Welfare of Its Members with Products Owned by the Nasari Cooperative, Trying to provide low interest rates and allowing retirees those aged over 70 years make loans, Increase Cooperative Capital, namely by increasing member's mandatory savings, and opening unlimited deposits. There are 3 obstacles faced by the Nasari Lhokseuawe Joint Welfare Cooperative in improving the welfare of its members, namely limited capital, sharia regulations, and the many competitors who also provide loans to retired customers so that they have to compete with the Nasari Cooperative, the Lhokseumawe branch. And the strategy carried out by the Nasari Lhokseuawe Cooperative in overcoming obstacles in improving the welfare of its members is by opening deposits that are not covered for customers or other people who want to deposit their money, following the applicable sharia rules, and providing the best service to customers so they can compete with another competitor.